Tunable Topological Phase Transition in Two-Dimensional Ternary Transition Metal Halides TiXI (X = P and As) - Chen, Peng-Jen (Frontiers in Materials, 2022)
With first-principles calculations we predict tunable topological phase transition in two-dimensional (2D) ternary transition metal halides alpha-TiXI (X = P and As) via strain engineering. Besides, changing the number of stacking layers or van der Waals interlayer spacing can also result in topological phase transition in few-layer TiXI. The on-site Coulomb U of Ti atoms is neither tunable nor empirical in this work. Instead, it is evaluated by the density functional perturbation theory and hence the results are more accurate. The tunable topological phase of 2D alpha-TiXI via strain engineering makes them promising in spintronics devices that exploit quantum spin Hall effect. Furthermore, the topological edge states of the single-layer TiAsI exhibit interesting feature. They do not cross at the time-reversal invariant momenta (TRIM) where the band inversion occurs. Instead, they extend over the whole one-dimensional Brillouin zone and cross at the other TRIM. While all requirements of Z2 topological phase are fulfilled, it is rare especially for those with direct gap. The linear bulk bands around and at Gamma may be the reason for the unusual crossing.